Republic of Korea : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The paper discusses potential output, the output gap, and inflation in Korea. The paper explores the information content of potential leading indicators of inflation. A broadly balanced current account has been the suggested norm for Korea over the medium term. The challenge is to help build a more robust bond market that prices risk appropriately. The features of pension schemes in Korea and the problems they face are outlined. The paper reviews pension reform, banking sector, corporate sector, and foreign exchange crises with respect to Korea.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet